Using impact monitoring mouthguards to measure head impact exposure in elite ice hockey - Mikael Swarén; Madelen Fahlstedt (JSAMS Plus)
Background: Even though women's ice hockey does not permit deliberate checking between players, female players are at similar or even higher risk to sustain concussions, as male players. Several studies have investigated head impacts in ice hockey, however to the best of the authors' knowledge, no previous study has used impact monitoring mouthguards to investigate head impact exposure among professional female ice hockey players. Methods: Impact monitoring mouthguards were used to collect head impact data during games in the Swedish Women's Hockey League and in the men's Swedish J20 SuperElite League in 2020. Results: Female players had significantly higher median linear accelerations than male players (26 [19–35] g, vs. 7 [5–9] g, p ​< ​0.001, d ​= ​1.98). Female players had significant higher median rotational accelerations compared to male players (3076 [2314–4243] rad/s2 vs. 430 [281–752] rad/s2, p ​< ​0.001, d ​= ​2.398). There were no notable variances in impact distribution by location for linear or rotational accelerations among female players. Similarly, male players didn't exhibit significant differences in impact location for linear acceleration. However, impacts at the Top Front location demonstrated significantly higher rotational accelerations compared to those at Front Low and Front High positions. Conclusion: Compared to male players, female players sustain fewer but harder impacts to the head, which may explain the high occurrence of concussion in women's ice hockey.